Edukasi Pencegahan Stunting di Desa Pagar Jati - Ahmad Syarifin; Depi Putri Wahyuni; Aini Aini; Elyshia Retnowati; Amin Sutejo (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Stunting is a chronic malnutrition problem caused by a lack of nutritional intake over a long period of time. Stunting is a major problem for areas with limited access to Health and Education resources. Community service was carried out in Pagar Jati Village, Semidang Lagan District, Central Bengkulu Regency regarding stunting prevention. The problem encountered was the number of toddlers or children affected by stunting in Pagar Jati Village, measured by the children's height which was lower compared to their age standard. This service aims to provide educational outreach regarding information regarding the characteristics, causes, impacts and ways to prevent stunting for residents of Pagar Jati Village. Apart from that, it provides comprehensive education or understanding to the public regarding the importance of good parenting and healthy eating patterns. The targets of this education are toddlers and children affected by stunting, teenagers, pregnant and breastfeeding mothers and village residents in general. The output of this outreach is by increasing community knowledge and awareness about children's nutritional needs and effective parenting practices, it is hoped that village residents can prevent and treat stunting efficiently and effectively so that the stunting rate in Pagar Jati Village can be minimized significantly.